Evaluation and comparison of a flumethrin-imidacloprid collar and repeated monthly treatments of fipronil/(s)-methoprene to control flea, Ctenocephalides f. felis, infestations on cats for eight months - Dryden, Michael W.; Smith, Victorene E.; Davis, W. L.; Settje, T.; Hostetler, J. (My University, 2016)
Background: This controlled laboratory study was designed to evaluate the efficacy of the 10 % imidacloprid/4.5 % flumethrin collar (Seresto (R), Bayer Animal Health) against fleas (Ctenocephalides f. felis) on cats, when compared to fipronil (9.8 % w/w)/(s)-methoprene (11.8 % w/w) topical spot-on formulation (Frontline (R) Plus for Cats and Kittens, Merial). Methods: Thirty cats were randomized into three groups of ten animals based on pre-treatment flea counts: Group 1: imidacloprid/flumethrin collar; Group 2: fipronil/(s)-methoprene topical spot-on and Group 3: non-treated controls. The imidacloprid/flumethrin collars were applied one time on Day 0, while the fipronil/(s)-methoprene spot-on was administered every 30 days from Day 0 through Day 210. Cats were infested with 100 fleas on study days 0, 7, 14, 29, 59, 89, 119, 149, 179, 209 and 239. All flea counts were conducted by combing to remove fleas on post-treatment days 2, 8, 15, 30, 60, 90, 120, 150, 180, 210 and 240. Results: The efficacy of the imidacloprid/flumethrin collar ranged from 98.2 to 100 % for eight months. The efficacy of fipronil/(s)-methoprene spot-on ranged from 68.2 to 99.9 %. Efficacy was < 85 % for fipronil/(s)-methoprene on Days 90, 150 and 210. The flea counts in both treatment groups were significantly fewer than those in the non-treated control group at every post-treatment study day (P < 0.0001). In addition, there were significantly fewer fleas in the imidacloprid/flumethrin collar group when compared to the fipronil/(s)-methoprene group on Days 90, 150 and 210 (P < 0.0001). Conclusions: This study demonstrated that the imidacloprid/flumethrin collar (Seresto (R), Bayer Animal Health) maintained excellent (> 98.2 %) efficacy against fleas on cats for the entire 8 month study. Monthly applications of fipronil/(s)-methoprene (Frontline (R) Plus for Cats and Kittens, Merial) generally had high, but variable (68.2 to 99.9 %) efficacy over the course of the eight month study. Based on the very high residual efficacy achieved by the imidacloprid/flumethrin collar in this study, veterinarians should expect that this collar will control and eliminate existing flea infestations on cats and in their in-home premises as long as every flea infested host is treated.
Citation: Dryden, M. W., Smith, V., Davis, W. L., Settje, T., & Hostetler, J. (2016). Evaluation and comparison of a flumethrin-imidacloprid collar and repeated monthly treatments of fipronil/(s)-methoprene to control flea, Ctenocephalides f. felis, infestations on cats for eight months. Parasites & Vectors, 9, 6. doi:10.1186/s13071-016-1575-5
Keywords: Ctenocephalides F. Felis; Cat Flea; Imidacloprid; Flumethrin; Fipronil; (S)-Methoprene